Genome-based reclassification of Azospirillum brasilense Sp245 as the type strain of Azospirillum baldaniorum sp. nov. Issue 12 (16th December 2020) - dos Santos Ferreira, Natalia; Hayashi Sant' Anna, Fernando; Massena Reis, Veronica; Ambrosini, Adriana; Gazolla Volpiano, Camila; Rothballer, Michael; Schwab, Stefan; Baura, Valter Antonio; Balsanelli, Eduardo; Pedrosa, Fabio de Oliveira; Pereira Passaglia, Luciane Maria; Maltempi de Souza, Emanuel; et al.
Abstract : Azospirillum sp. strain Sp245 T, originally identified as belonging to Azospirillum brasilense, is recognized as a plant-growth-promoting rhizobacterium due to its ability to fix atmospheric nitrogen and to produce plant-beneficial compounds. Azospirillum sp. Sp245 T and other related strains were isolated from the root surfaces of different plants in Brazil. Cells are Gram-negative, curved or slightly curved rods, and motile with polar and lateral flagella. Their growth temperature varies between 20 to 38 °C and their carbon source utilization is similar to other Azospirillum species. A preliminary 16S rRNA sequence analysis showed that the new species is closely related to A. brasilense Sp7 T and A. formosense CC-Nfb-7 T . Housekeeping genes revealed that Azospirillum sp. Sp245 T, BR 12001 and Vi22 form a separate cluster from strain A. formosense CC-Nfb-7 T, and a group of strains closely related to A. brasilense Sp7 T . Overall genome relatedness index (OGRI) analyses estimated based on average nucleotide identity (ANI) and digital DNA–DNA hybridization (dDDH) between Azospirillum sp. Sp245 T and its close relatives to other Azospirillum species type strains, such as A. brasilense Sp7 T and A. formosense CC-Nfb-7 T, revealed values lower than the limit of species circumscription. Moreover, core-proteome phylogeny including 1079 common shared proteins showed the independent clusterization of A. brasilense Sp7 T, A. formosense CC-Nfb-7 T and Azospirillum sp. Sp245 T, a finding that was corroborated by the genome clustering of OGRI values and housekeeping phylogenies. The DNA G+C content of the cluster of Sp245 T was 68.4–68.6 %. Based on the phylogenetic, genomic, phenotypical and physiological analysis, we propose that strain Sp245 T together with the strains Vi22 and BR12001 represent a novel species of the genus Azospirillum, for which the name Azospirillum baldaniorum sp. nov. is proposed. The type strain is Sp245 T (=BR 11005 T =IBPPM 219 T ) (GCF_007827915.1, GCF_000237365.1, and GCF_003119195.2).